Effective defluoridation of industrial wastewater by using acid modified alumina in fixed-bed adsorption column: Experimental and breakthrough curves analysis. (10th January 2021) - Kumari, Usha; Mishra, Asmita; Siddiqi, Hammad; Meikap, B.C.
Abstract: The defluoridation performance of a simple and efficient adsorbent (SAA), developed by H2 SO4 treatment of alumina, was explored in fixed-bed adsorption column (FBAC). The SAA was characterized by SEM, EDX, FTIR, XRD and Raman spectroscopy. The influence of different process affecting parameters like bed depth (2.5–7.5 cm), influent flow rate (1.5–2.5 mL/min), and fluoride concentration (40–60 mg/L) were explored. The increased bed depth, and reduced flow rate and fluoride concentration were found to improve the column performance. The fitting of Thomas, Yoon-Nelson, Clark, BDST, and Yan models to breakthrough curves were attempted. The best fitting (R 2  > 0.9) was exhibited by Clark model. The column exhibited the maximum performance at bed depth of 7.5 cm, influent flow rate of 1.5 mL/min, and fluoride concentration of 40 mg/L. The column performance of SAA was superior to unmodified alumina. The SAA (5 g) demonstrated the successful result (% R = 89.76%; tb  = 350 min; te  = 1037 min) for the treatment of industrial effluent (16.54 mg/L) in FBAC. Besides, the column loaded by SAA exhibited reusability up to four cycles. These results implied the suitability of SAA for the treatment of fluoride contaminated industrial wastewater or groundwater in continuous operating mode. Graphical abstract: Image 1 Highlights: Fixed bed adsorption column loaded by SAA adsorbent was able to meet 1.5 mg/L limit of defluoridation. Thomas, Yoon-Nelson, Clark, Yan and BDST models fitted well to breakthrough curves. Sulphuric acid modified alumina (tb  = 353 min) had better column performance than the parent alumina (tb  = 3 min). Efficient defluoridation (89.76% removal; tb  = 350 min; te  = 1037 min) of industrial wastewater by SAA (5 g) loaded FBAC. Column was successfully reused up to four cycles by applying NaOH as desorption reagent.